CEvADA: Co-Evolution Analysis Data Archive - da Fonseca Júnior, Neli José; Afonso, Marcelo Querino Lima; Bleicher, Lucas (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2021: Anais do XIV Simpósio Brasileiro de Bioinformática, 2021)
CEvADA is a database of amino acid coevolution networks aimed to detect specificity determinant and function related sites in protein families. The database was also designed to provide an easy access to protein coevolutionary constraints that can be incorporated in machine learning classification models, just as sequence annotation and structure prediction methods. The data can be accessed for the whole protein family and specific protein sequences. We also provide sequence search and a REST API for programmatic access in the database. The current version of the database contains data related to 6.301 conserved domains and 45 million protein sequences. CeVADA is free and can be accessed at http://bioinfo.icb.ufmg.br/cevada .